Investigating six-degree-of-freedom loading of shallow foundations on sand - Bienen, B; Byrne, B; Houlsby, G; Cassidy, M (Thomas Telford Ltd., 2006)
Laboratory studies of the response of shallow foundations have previously considered only planar loading. This paper describes experimental work carried out using a loading device that applies general loading onto model shallow foundations. The loading, involving all six degrees of freedom [vertical (V), horizontal (H2, H3), torsion (Q) and overturning moment (M2, M3)], has been applied to a 150 mm diameter circular flat rough foundation on a loose dry silica sand. Aspects of the loading rig design are briefly described, but the main focus is the presentation of the experimental results. These provide evidence for the generalisation of existing work-hardening plasticity models from planar loading to general loading conditions. This evidence is used to extend an existing numerical model to the six-degree-of-freedom case, and the simulation results are compared with the experimental results.